2012
DOI: 10.1105/tpc.111.093674
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Evolution of Nucleotide Landscapes in Seed Plants

Abstract: Nucleotide landscapes, which are the way base composition is distributed along a genome, strongly vary among species. The underlying causes of these variations have been much debated. Though mutational bias and selection were initially invoked, GC-biased gene conversion (gBGC), a recombination-associated process favoring the G and C over A and T bases, is increasingly recognized as a major factor. As opposed to vertebrates, evolution of GC content is less well known in plants. Most studies have focused on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
113
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 96 publications
9
113
0
Order By: Relevance
“…If so, this lower recombination might also result in a reduced frequency of repair at heterologous recombination sites. This type of repair preferentially introduces GC bases (47), and it has been suggested to be one of the few mechanisms responsible for maintaining the high GC richness of genes and perhaps, other regions of DNA in the genome (11,23,32). However, clearly, more experimental and detailed genomic data are needed from plant and animal species with holocentric chromosomes before attempting any generalization Dataset S1, Tables S3 and S4 shows the results of variables not incorporated into the final model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If so, this lower recombination might also result in a reduced frequency of repair at heterologous recombination sites. This type of repair preferentially introduces GC bases (47), and it has been suggested to be one of the few mechanisms responsible for maintaining the high GC richness of genes and perhaps, other regions of DNA in the genome (11,23,32). However, clearly, more experimental and detailed genomic data are needed from plant and animal species with holocentric chromosomes before attempting any generalization Dataset S1, Tables S3 and S4 shows the results of variables not incorporated into the final model.…”
Section: Resultsmentioning
confidence: 99%
“…To date, the highest GC contents of land plants have been found in grasses (Poaceae) (11,15,(29)(30)(31)(32)(33)(34). Although grasses are reported to have undergone a dramatic spread and evolutionary diversification over the last ∼30 My as the climate has become increasingly arid and cool (35)(36)(37), the reasons underpinning their success are controversial given that grasses have extremely desiccation-sensitive (recalcitrant) pollen (38), a feature certainly not well-suited for growth in arid environments (39).…”
Section: Significancementioning
confidence: 99%
“…According to this model, GC-biased gene conversion results from the GC bias of the mismatch repair machinery, so highly recombinogenic genes, which would form heteroduplexes at a higher frequency, would tend to be more GC rich. Recently, it was shown that grasses, in general, display strongly decreasing GC gradients along transcripts (42), and it was suggested that GC-biased gene conversion would explain them if gene conversion was higher at the 5′ end of grass genes. Except for the sharp reversal at the 3′ end, which may not be a universal feature of bz haplotypes, the 5′ to 3′ bz gene conversion gradient described here would support that suggestion.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the association between seedling MNase HS regions and recombination hotspots, we tested whether MNase HS regions are also enriched for tracts of GC-biased gene conversion. Conversion tracts arise when base mismatches at recombination junctions resolve in favor of G+C nucleotides relative to A+T nucleotides (15,16). We assessed the historical influence of GC-biased gene conversion on the maize lineage, using PHASTbias with an alignment of 12 monocots and eudicots (17), although limiting the alignment to only grasses had no significant effect (SI Appendix, Fig.…”
Section: Strong Sustained Gc-biased Gene Conversion Surrounds Mnase Hsmentioning
confidence: 99%